Teaching modern heuristics in combinatorial optimization : The example of a demonstration and research tool employing metaheuristics in scheduling - Geiger, Martin Josef (2006)
The article describes the proposition and implementation of a demonstration, learning and decision support system for the resolution of combinatorial optimization problems under multiple objectives. The system brings together two key aspects of higher education: research and teaching. It allows the user to define modern metaheuristics and test their resolution behavior on machine scheduling problems. The software may be used by students and researcher with even little knowledge in the mentioned field of research, as the interaction of the user with the system is supported by an extensive graphical user interface. All functions can be easily parameterized, and expensive software licenses are not required. In order to address a large number of users, the system is localizable with little effort. So far, the user interface is available in seven languages. The software has been honored in Ronneby (Sweden) with the European Academic Software Award 2002, a prize for learning and research software awarded biannually by EKMA, the European Knowledge Media Association (http://www.easa-award.net/, http://www.bth.se/llab/easa_2002.nsf).